CHROMATOGRAPHY-BASED PARTIAL PURIFICATION AND CHARACTERIZATION OF ANTIMICROBIAL COMPOUND ISOLATED FROM A TERRESTRIAL STREPTOMYCES - Kesavan S, Sudha Sri; S, Usha Nandhini; Vasudevan, Girija (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: A potent Streptomyces strain isolated from garden soil samples of Sathyabama University, Chennai, and the characterization and its antimicrobial activity was reported previously. This report deals with partial purification and characterization of the partially purified antimicrobial compound by liquid chromatography-mass spectrum (LC-MS) method. Method: The crude extract was characterized by ultra violet-visible spectrum (UV) and Fourier transform infrared spectroscopy (FTIR) subsequently partial purification was done by thin-layer chromatography, and the bands were used for LC-MS analysis. The obtained mass spectrum was searched in NIST for species data by molecular weight. The compound was identified by comparing the mass spectrum with the known compounds mass spectrum having 98-100% identical. The biological activity of the identified compound was searched in PubChem. Results: The UV and FTIR spectrum indicate the presence of hydroxyl group, aliphatic chain, aromatic, aliphatic amines, and ethers in the crude extract. The LC-MS spectrum revealed the presence of 12 compounds in high intensity resembling antimicrobial compounds such as imidazole, N-trifluoroacetyl, cyclohexane, 2-nitro, and stigmasterol. Conclusion: The instrumental analysis shows the presence of 14 different compounds, and PubChem compound search shows these compounds having various biological activities including antibacterial, antifungal, anticancer, antitumor, and antidepressant. This report insists us further to evaluate the anticancer, antitumor, and antitrypanosomal activities of the partially purified compound.